Do the effects of high intensity 40 km cycling upon left ventricular function and cardiac biomarker during recovery vary with time of day? - Chan-Dewar, F.; Gregson, W.; Whyte, G.; Gaze, D.; Waterhouse, J.; Wen, J.; George, K. (Journal of Sports Sciences, 2013)
Twelve healthy participants performed two identical high-intensity 40 km cycling trials (morning and evening) under controlled laboratory conditions. Echocardiograms and venous blood samples were collected before and after each exercise bout. Cardiac electro-mechanical-delay (cEMD) was measured as QRS-complex onset to peak systolic (S`) and early diastolic (E`) tissue velocities. Myocardial strain and strain rates were assessed in longitudinal, circumferential and radial planes at the left ventricular apex and base. Cardiac troponin I (cTnI) and N-terminal Pro-Brain Natriuretic Peptide (NT-proBNP) were assessed as biomarkers of cardiomyocyte damage and wall stress. cEMD was lengthened after both morning (S`: 160 ± 30 vs. 193 ± 27; E`: 478 ± 60 vs. 620 ± 87, P < 0.05) and evening (S`: 155 ± 29 vs. 195 ± 31; E`: 488 ± 42 vs. 614 ± 61, P < 0.05) trials. A reduction in peak S` (morning: 6.96 ± 1.12 vs. 6.66 ± 0.89; evening: 7.09 ± 0.94 vs. 7.02 ± 0.76) was correlated with cEMD (r = -0.335, P < 0.05). Peak longitudinal strain was reduced, atrial strain rates were sporadically increased in both trials post-cycling. cTnI was elevated in only two participants (0.04 µg · L-1, 0.03 µg · L-1), whilst NT-proBNP was below the clinical cut-off point in all participants. Prolonged-cycling resulted in a lengthening of cEMD, small changes in aspects of left ventricular deformation and sporadic increases in cardiac biomarkers. None of these effects were moderated by time-of-day.